Room temperature, metal-free, CDI-promoted, ex-situ protocol for S-methyl thioester synthesis - Manisha A. Patel; Vandana Sharma; Rupali Chavan; Juhi Pal; Santosh J. Gharpure; Anant R. Kapdi (Scientific Reports)
Abstract S-methyl thioesters have proven to be useful intermediates in many biosynthetic reactions and their occurrence in bioactive molecules further enhance their appeal. Shortcomings in several reported synthetic protocols have led us to disclose herewith a mild, room temperature ex situ protocol that provides access to a large number of thioesters (aryl, heteroaryl, alkyl, amino acids). Late-stage functionalization strategies were also performed on commercial pharmaceutical drugs (containing carboxylic acid functionality) while further in situ conversion to valuable compounds has also been achieved.